Intellectual Stress of Basic Education Faculty Professors (Journal of the College of Education for Women, 2019)
1-Identifying the intellectual exertions have basic education faculty professors.2-. Identifying the differences in intellectual exertions as a variable type (male-female) current research society is determined by the basic education college professors and both sexes Mustansiriyah University and academic year (2018-2019) and sample (200) textbook and teaching staff researcher has built a scale term This intellectual and extract his results showed statistical characteristics:-. The College of basic education teachers suffer from stress. There were no differences between males and females in intellectual exertions. Depending on the results, the researcher has developed a number of recommendations and proposals Keywords: stress – professors – basic education